The Outcome of Intracoronary Tirofiban Administation at Primary Percutenous Coronary Intervention in ST-Elevation Myocardial Infarction Patients - Muhammad Umar Iqbal, Mudassar Iqbal, Asif Ali, Saqib Riaz, Urwah Imtiaz, Khursheed Ahmad (Pakistan Journal of Medical & Health Sciences, 2023)
Background and Aim: Thrombosis within the coronary arteries causes ST-elevation myocardial infarction. STEMI can be vascularized by primary PCI, which is class-I indication and the gold standard. The present study aimed to assess the outcome of pericardial tirofiban administration in patients with ST-level myocardial infarction following primary percutaneous coronary intervention. Patients and Methods: This cross-sectional study was conducted on 228 ST-elevation myocardial infarction (STEMI) patients in the Bahawalpur Heart Center, Bahawalpur for the duration of Six months from March 2022 to September 2022. Patients of both gender having an age range 25 to 65 years with STEMI were enrolled and categorized into two groups based on Tirofiban administration are as follows: Group-I comprised of Tirofiban group and Group-II control (non-tirofiban group). All the patients underwent primary percutaneous coronary intervention (PCI). Major bleeding, MACE, TIMI Grade flow, hematoma, myocardial blush, minor bleeding, and mortality were different variables measured. SPSS version 28 was used for data analysis. Results: The overall mean age was 42.82± 10.26 years. Of the total 228 STEMI patients, there were 166 (72.8%) male and 62 (27.2%) were females. The mean age of group-I (n=114) and group-II (n=114) was 41.74 ± 11.62 years and 43.9± 8.9 years. The age-wise distribution of patients were as follows: 74 (32.5%) in 25-35 years, 70 (30.7%) in 36-45 years, 64 (28.1%) in 46-55 years, and 20 (8.8%) in 56-65 years. The prevalence of hypertension, diabetes, and smoker in Tirofiban and non-tirofiban group was 32 (28.1%) vs. 34 (29.8%), 24 (21.1%) vs. 28 (24.6%), and 31 (27.2%) vs. 33 (28.9%) respectively. A p-value of 0.05 indicated that there was an independent difference in TIMI flow grades between the two groups. Based on clinical outcomes, the incidence of partial reperfusion TIMI flow grade, normal myocardial blush grade, major bleeding, MACE, hematoma, minor bleeding, and mortality was found in 72 (31.6%), 146 (64%), 60 (26.3%), 68 (29.8%), 61 (26.8%), 52 (22.8%), and 8 (3.5%) respectively. Conclusion: The present study found that patients with severe thrombus burden and STEMI who underwent emergency coronary intervention received intracoronary tirofiban treatment that was simple, safe, and effective. A significant difference in TIMI flow and myocardial blush grades was observed when intracoronary Tirofiban was administered to STEMI patients undergoing percutaneous coronary intervention compared with patients who did not receive intracoronary Tirofiban. Keywords: Intracoronary Tirofiban, Percutaneous coronary intervention, ST-elevation myocardial infarction, Outcomes